2007
DOI: 10.1111/j.1467-8683.2007.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Board Composition and its Monitoring Committees on Earnings Management: evidence from Spain

Abstract: We test whether corporate governance mechanisms promoted by best practice codes are effective in constraining earnings manipulation for a Spanish sample of quoted companies during the period 1999-2001. In particular, we analyse the association between earnings management and two key aspects of corporate governance: board composition and the existence of board monitoring committees. Our results show that board composition significantly determines earnings manipulation practices. However, the main role in constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(67 citation statements)
references
References 47 publications
4
55
0
2
Order By: Relevance
“…In fact, previous evidence obtained for the Spanish case seems to support this latter view by highlighting the ineffectiveness of ACs which were set up during the voluntary period (Fuentes Barbera et al 2005;García Osma and Gill de Albornoz 2007;Pucheta and De Fuentes 2007). However, companies that created their ACs after the enactment of the the Financial System Reform Law (2002) have been forced to comply with a series of requirements regarding the composition of the AC and the functions to be carried out.…”
Section: Literature Review and Hypothesesmentioning
confidence: 56%
See 2 more Smart Citations
“…In fact, previous evidence obtained for the Spanish case seems to support this latter view by highlighting the ineffectiveness of ACs which were set up during the voluntary period (Fuentes Barbera et al 2005;García Osma and Gill de Albornoz 2007;Pucheta and De Fuentes 2007). However, companies that created their ACs after the enactment of the the Financial System Reform Law (2002) have been forced to comply with a series of requirements regarding the composition of the AC and the functions to be carried out.…”
Section: Literature Review and Hypothesesmentioning
confidence: 56%
“…However, other studies have not shown any connection between the quality of the financial information and the existence of an AC or with its structure and workings (Fuentes Barbera et al 2005). Similarly, other studies have arrived at the conclusion that the presence of an independent AC does not affect the quality of accounting information (García Osma and Gill de Albornoz 2007) and that neither the existence nor the composition of the AC have an influence on the tendency to receive qualified opinions in the audit reports (Pucheta and De Fuentes 2007). Analysing the period during which it has been compulsory to set up ACs, a similar conclusion is reached that there is not a significant association between AC and earnings quality (Monterrey Mayoral et al 2008).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies (Klein, 2002a;Peasnell, Pope & Yong, 2005;Osma & Noguer, 2007) have examined some key elements of boards' monitoring activities, such as the proportion of outside board members, and the structure of the board and its committee. These key elements affect the strength of the boards' monitoring activities.…”
Section: Board Monitoring and Earnings Managementmentioning
confidence: 99%
“…It is expected that the more independent the board of directors is, the less earnings manipulation will be possible for the managers (Chtourou et al, 2001;Davidson et al, 2005;Osma, & Naguer, 2007;Peasnell et al, 2005). However, considering family businesses, there arise some specific and characteristic agency issues, such as the owning family's pursuit of its own economic interests; its pursuit of its own non-economic interests; the parental tendency to act upon altruistic motives; and the different nuclear family units' pursuit of their own interests (Bammens, Voordeckers, & Gils, 2011).…”
Section: The Board Of Directors and Em In Family-owned Firmsmentioning
confidence: 99%